Applications of quasi-uniform codes to storage - Thomas, Eldho K. (2015)
We consider the design of quasi-uniform codes from dihedral 2-groups. Quasi-uniform codes have the distinctive feature of allowing codeword coefficients to live in different alphabets. We obtain a bound on the minimum distance of quasiuniform codes coming from p-groups as a function of the number of p-ary codeword components. We study possible applications of such codes to storage, where the minimum distance is important to allow object retrieval, yet binary coefficients are preferred for fast computations, for example during repairs.